PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS TERPADU KELAS VII DI SMP NURUL HUDA KAPONGAN SITUBONDO - Lailatus Syamsiyah; Dassucik Dassucik; Tri Astindari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2021)
Giving reward and punishment is something that cannot be separated. If it is applied separately, it will not work effectively, especially in strengthening discipline. This study aims to determine the effect of giving rewards and punishments on students' interest in learning in integrated social studies subjects for class VII SMP Nurul Huda Kapongan Situbondo even semester of the 2020/2021 school year. This research uses Ex Post Facto research. The population in this study is the seventh grade in the even semester of SMP Nurul Huda Kapongan Situbondo. Data collection in this study was carried out using observation, questionnaires, and documentation and then analyzed by Chi-Square Test. the results of the analysis of the data obtained by using the Chi-Square test analysis formula produces hit of 14.394 hit. And a significance level of 5% obtained tab 3.841, meaning that the hit price is 14.394 > the tab price is 3.841. So it can be concluded that there is an effect of giving rewards and punishments on students' interest in learning in the Integrated Social Studies subject for class VII even semester of SMP Nurul Huda Kapongan Situbondo. The results of the analysis using the contingency coefficient formula (KK) obtained a correlation coefficient of 0.63. After being consulted with the interpretation table above, the value of 0.63 lies between ± 0.61 to ± 0.80 then the level of correlation between the effect of reward-punishment on students' interest in learning is high correlation.